Local council members' view on inter-municipal cooperation: Does office-related self interest matter? - Christian Bergholz; Ivo Bischoff (Philipps-University Marburg, School of Business and Economics, 2016)
We analyze data from a survey among local council members in 59 German municipali-ties. We ask council members whether their home municipality should cooperate with neigh-boring municipalities in the provision of public services like childcare or road maintenance. Their answers are clearly driven by office-related self-interest. Council members who have more political power and thus have more power to lose if their home municipality cooperates are more likely oppose inter-municipal cooperation. This interpretation receives further backing by the fact that delegates' support for inter-municipal cooperation increases in the population size of their home municipality but decreases in the size of its neighbors.
Keywords: H77; D72; 330; inter-municipal cooperation; politicians; survey; Germany; public choice